2014
DOI: 10.2174/1874192401408010061
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome in the Young: Clinical Characteristics, Risk Factors and Prognosis

Abstract: Background:To describe the characteristics of patients ≤40 years of age hospitalized for acute coronary syndrome, analyze the risk factors and identify the variables associated with prognosis.Methods:Case series of patients admitted between 2003 and 2012 inclusive in a tertiary hospital (123 consecutive cases admitted between 2003 and 2012), and case-control study (369 controls selected from the general population matched for sex and age with cases, at a ratio of 3:1). Outcome variables: Mortality, likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
3
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 24 publications
10
46
3
14
Order By: Relevance
“…Andrés et al [22] reported an even greater disproportion between young (< 46 years) and older patients: 2.77% vs. 13.65%, respectively. At the same time, there is a great risk of cardiovascular rehospitalisation, especially if the patient continues to smoke [32]. The results of studies by Nielsen et al [33] should therefore come as no surprise, wherein long-term mortality in young patients after MI, albeit low, remains two to four times higher than in the general male population, and even higher in women.…”
Section: Prognosis and Secondary Preventionmentioning
confidence: 98%
“…Andrés et al [22] reported an even greater disproportion between young (< 46 years) and older patients: 2.77% vs. 13.65%, respectively. At the same time, there is a great risk of cardiovascular rehospitalisation, especially if the patient continues to smoke [32]. The results of studies by Nielsen et al [33] should therefore come as no surprise, wherein long-term mortality in young patients after MI, albeit low, remains two to four times higher than in the general male population, and even higher in women.…”
Section: Prognosis and Secondary Preventionmentioning
confidence: 98%
“…In the last years many papers have regarded the acute coronary syndromes [18,42] and the myocardial infarction in young patients [6,21] although in these reports the age considered has been respectively of 35 years [42], of 40 years [6,18], and between 30 and 54 years [21].…”
Section: Conclusive Considerationsmentioning
confidence: 99%
“…7 Það er því tímabaert að kanna á ný stöðu mála í yngsta sjúklingahópnum sem í fyrri rannsókninni reyndist hafa margs konar sérstöðu miðað við aðra aldurshópa 6 en þó áþekka því sem lýst hefur verið í mörgum erlendum rannsóknum. [3][4][5][8][9][10][11][12][13][14] Markmið þessarar rannsóknar var því að kanna hver þróunin hefur orðið meðal ungra þolenda alvarlegs kransaeðasjúkdóms og áherslan, eins og í fyrri rannsókninni, á nýgengi, áhaettuþaetti og afdrif, sem og á útbreiðslu kransaeðaþrenginganna.…”
Section: Inngangurunclassified
“…9 Í mörgum rannsóknum virðist tilhneiging vera í þá átt að hlutfall kvenna meðal ungra einstaklinga með brátt hjartadrep fari haekkandi.…”
Section: Umraeðaunclassified
See 1 more Smart Citation